Dual language instruction : - Cloud, Nancy (Heinle & Heinle, 2000)
Dual Language Instruction: A Handbook for Enriched Education is an ideal professional reference title for those interested in teaching ESL, foreign language, and bilingual programs. It ts a resource guide for implementing, evaluating, administering, and maintaining dual language instruction programs.